Dinamika Hijrah di Indonesia: Dari Transformasi Spiritual Menuju Gerakan Sosial: The Dynamics of Hijrah in Indonesia: From Spiritual Transformation to Social Movement - Hakim, Lukman (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
The phenomenon of Hijrah in Indonesia has transformed from a spiritual journey into a broad social movement, involving various communities with diverse historical backgrounds and socio-political contexts. This study aims to explore the Hijrah phenomenon within the Indonesian context by examining shifts in its meaning and practices, as well as understanding its transformation into a social movement that influences religious identity and social interactions. Employing a qualitative methodology, this study focuses on a literature review and an interpretive approach to grasp the Hijrah phenomenon from historical, social, cultural, and spiritual perspectives. The findings reveal that Hijrah has evolved from the concept of physical migration to encompass changes in attitude, lifestyle, and Islamic dress codes, reflecting repentance and the religious aspirations of a new generation. Additionally, Hijrah serves as a medium for disseminating doctrine and carries specific socio-economic impacts. This study concludes that Hijrah in Indonesia is a multidimensional phenomenon, reflecting the dynamic social, cultural, and religious fabric of the society. The transformation of Hijrah into a social movement not only alters the religious landscape but also influences social, economic, and political interactions. This study emphasizes the importance of a multidisciplinary approach in understanding contemporary religious and social dynamics. Abstrak Fenomena hijrah di Indonesia telah mengalami transformasi dari perjalanan spiritual menjadi gerakan sosial yang luas dan melibatkan berbagai komunitas dengan latar belakang historis dan konteks sosio-politik beragam. Kajian ini bertujuan untuk mengeksplorasi fenomena hijrah dalam konteks Indonesia dengan menelaah pergeseran makna dan praktiknya, serta memahami transformasinya menjadi gerakan sosial yang mempengaruhi identitas religius dan interaksi sosial. Kajian ini menggunakan metode kualitatif, dengan fokus studi kepustakaan dan pendekatan interpretatif untuk memahami fenomena hijrah dari perspektif historis, sosial, budaya, dan spiritual. Kajian ini menunjukkan bahwa hijrah telah berkembang dari konsep migrasi fisik menjadi perubahan sikap, gaya hidup, dan tata cara berpakaian yang lebih Islami, mencerminkan pertobatan dan aspirasi religius generasi baru. Hijrah juga menjadi medium penyebaran doktrin dan memiliki dampak sosio-ekonomi tertentu. Kajian ini menyimpulkan bahwa hijrah di Indonesia merupakan fenomena multidimensi yang mencerminkan dinamika sosial, kultural, dan religius masyarakat. Transformasi hijrah menjadi gerakan sosial tidak hanya mengubah landscape keagamaan tapi juga mempengaruhi interaksi sosial, ekonomi, dan politik. Kajian ini menegaskan pentingnya pendekatan multidisipliner dalam memahami dinamika keagamaan dan sosial kontemporer.